2022
DOI: 10.1002/cyto.b.22062
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric immunophenotyping of plasma cells across the spectrum of plasma cell proliferative disorders: A fresh insight with pattern‐based recognition

Abstract: Background: The expression pattern of common antigens including cytoplasmic kappa/lambda ratio (cyKLR) was evaluated by flow cytometric immunophenotyping (FCMI) to explore their relevance in discriminating normal and aberrant plasma cells (NPC and APC, respectively) across spectrum of plasma cell proliferative disorders (PCPD).Methods: In this prospective analysis, 791 samples from PCPD (treatment naive = 455; partially treated = 336) were evaluated for expression of CD38, CD138, CD45, CD19, CD56, CD27, CD81, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Since samples for FCMI require a higher aspirate volume than cytomorphology, an extended pull‐out time is expected, causing peripheral blood contamination 7 . The morphological assessment can provide a measure of BMPC% but FCMI can delineate neoplastic from normal plasma cells and has thus proven to be a better tool for response assessment in PCPDs 8 . European Myeloma network has recommended use of first pull aspirate for minimal residual disease (MRD) assessment in MM by FCMI 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since samples for FCMI require a higher aspirate volume than cytomorphology, an extended pull‐out time is expected, causing peripheral blood contamination 7 . The morphological assessment can provide a measure of BMPC% but FCMI can delineate neoplastic from normal plasma cells and has thus proven to be a better tool for response assessment in PCPDs 8 . European Myeloma network has recommended use of first pull aspirate for minimal residual disease (MRD) assessment in MM by FCMI 9 .…”
Section: Introductionmentioning
confidence: 99%
“…7 The morphological assessment can provide a measure of BMPC% but FCMI can delineate neoplastic from normal plasma cells and has thus proven to be a better tool for response assessment in PCPDs. 8 European Myeloma network has recommended use of first pull aspirate for minimal residual disease (MRD) assessment in MM by FCMI. 9 However, at the diagnostic time point, the first pull BMA is served for cytomorphological evaluation despite the deteriorated sample quality of secondary pull BMA that may have a negative impact on special studies such as FCMI, cytogenetics and molecular investigations.…”
mentioning
confidence: 99%
“…In the second scenario, any PC population gated based on aberrant expression of surface markers and exhibiting abnormal cyKLR was defined as APC. Immunophenotypic aberrancies in APC in this study were defined based on differential expression of antigens on NPC and APC present within the same sample (Das et al, 2022). For aberrancy evaluation, MFI of each antigen on APC at diagnostic and post-therapy time point was compared with respect to the internal NPC within the same sample and MFI value lying above and below NPC population was defined as over-expression and under-expression, respectively.…”
Section: Definition Of Normal Reactive and Aberrant Plasma Cellsmentioning
confidence: 99%
“…This prospective analysis included 791 samples from PCPD using CD38, CD138, CD45, CD19, CD56, CD27, CD81, CD117, Cy‐kappa, and Cy‐lambda markers. The role played by these immunological markers in discriminating normal and aberrant plasma cells (NPC and APC, respectively) has been discussed, providing further insights into plasma cell characterization through the artificial eyes of flow cytometry (Das et al, 2022; Jevremovic & Olteanu, 2019; Mestrum et al, 2020; Oliveira et al, 2019; Zannetti et al, 2020; Zannetti et al, 2021).…”
mentioning
confidence: 99%
“…This prospective analysis included 791 samples from PCPD using CD38, CD138, CD45, CD19, CD56, CD27, CD81, CD117, Cy-kappa, and Cy-lambda markers. The role played by these immunological markers in discriminating normal and aberrant plasma cells (NPC and APC, respectively) has been discussed, providing further insights into plasma cell characterization through the artificial eyes of flow cytometry (Das et al, 2022;Jevremovic & Olteanu, 2019;Mestrum et al, 2020;Oliveira et al, 2019;Zannetti et al, 2020;Zannetti et al, 2021). Based on these findings, authors have concluded that CD200 is commonly expressed on circulating Sezary cells, a feature that can potentially improve the diagnostic capacity of flow cytometry for the assessment of T-cell neoplasms (Guitart, 2020;Horna et al, 2020;Lyapichev et al, 2020;Shameli & Roshan, 2022).…”
mentioning
confidence: 99%